Compreendendo a exceção: uma abordagem materialista-histórica ao direito a partir das reformas estruturais brasileiras pós-2016 - Rigato Filho, Roberto (2019)
This dissertation is a Marxist approach to law in the contemporary period, and aims to understand why the exceptions to legal norms, especially to those that give us the constitutional meaning, are so present and evident in the present historical stage. The empirical starting point, therefore, is the crisis of the normativity of law, and the fact that law bears its negation. Referring to the exceptional measures that restructured the Brazilian political matrix from 2016 and the specificity of current capitalism, this work starts from the theoretical basis of Marx and Pachukanis to relate the fragility of law as a normative standard and its need as a structure to the mode as capital predominates the becoming of men to rescue the value valorization process, in crisis